2018
DOI: 10.1002/hep.29798
|View full text |Cite
|
Sign up to set email alerts
|

Basolateral CD147 induces hepatocyte polarity loss by E‐cadherin ubiquitination and degradation in hepatocellular carcinoma progress

Abstract: Hepatocytes are epithelial cells with highly specialized polarity. The disorder and loss of hepatocyte polarity leads to a weakness of cell adhesion and connection, the induction of epithelial–mesenchymal transition, and eventually the occurrence of hepatocellular carcinoma (HCC). Cluster of differentiation 147 (CD147), a tumor‐related glycoprotein, promotes epithelial–mesenchymal transition and the invasion of HCC. However, the function of CD147 in hepatocyte depolarization is unknown. Here we identified that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 50 publications
5
62
0
1
Order By: Relevance
“…After excluding nonspecific antigenic interference, the integral optical density summary (IOD SUM) was obtained. All images were measured by using the same conditions . Based on the IOD SUM of Notch1, the patients were divided into two groups, Notch1‐High and Notch1‐Low according to the median value.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After excluding nonspecific antigenic interference, the integral optical density summary (IOD SUM) was obtained. All images were measured by using the same conditions . Based on the IOD SUM of Notch1, the patients were divided into two groups, Notch1‐High and Notch1‐Low according to the median value.…”
Section: Methodsmentioning
confidence: 99%
“…CD147, encoded by the BSG gene, is a type I transmembrane glycoprotein belonging to the immunoglobulin superfamily that is highly expressed in various cancer cells, such as breast cancer , non‐small cell lung cancer , and HCC. In HCC cells, overexpression of CD147 promotes dedifferentiation , invasion and migration of HCC cells and is significantly associated with the poor survival of patients with HCC . Moreover, studies have shown that CD147 is shed by ADAM10 , which is a precondition for hydrolysis by the γ‐secretase complex.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that CBLL1 plays an important role in tumorigenesis . First, CBLL1 expression is upregulated in human colon and gastric cancer tissues, and CBLL1 has been reported to induce anchorage‐dependent cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that CBLL1 plays an important role in tumorigenesis. [15][16][17][18][19][20][21][22][23][24] First, CBLL1 expression is upregulated in human colon and gastric cancer tissues, and CBLL1 has been reported to induce anchorage-dependent cell growth. In colorectal epithelial cells, the autocrine Slit-Robo pathway promotes CBLL1-mediated downregulation of E-cadherin to promote carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…CD147, a transmembrane glycoprotein, belongs to the immunoglobulin superfamily and is widely expressed on the surface of cancer cells . Reports showed that CD147 was over‐expressed in many types of cancer, such as human malignant melanoma, hepatocellular carcinoma, lung cancer, gastric cancer, breast cancer and so on . CD147 is also reported to involve in tumor progression, angiogenic function and immune response …”
Section: Introductionmentioning
confidence: 99%